Gambaran Kadar Gula Darah Penderita Tuberkulosis (TBC) di RSUD H. Andi Sulthan Daeng Radja Kabupaten Bulukumba - Awalia, Rizki; Ridwan, Asriyani; Islawati, Islawati (Universitas Sumatera Barat, 2024)
Tuberculosis (TB) is a chronic infection that not only affects the lungs but can also impact the body's metabolic system, including glucose regulation. In patients with comorbid diabetes mellitus (DM), the risk of elevated blood glucose levels is higher due to the added metabolic disruption from both conditions. Therefore, this descriptive study aims to illustrate fasting blood glucose levels in TB patients with DM at H. Andi Sulthan Daeng Radja Hospital, Bulukumba Regency. This study used purposive sampling and involved 30 TB patients with DM as the sample. Fasting blood glucose levels were measured using spectrophotometry to obtain accurate and detailed data regarding blood glucose levels. The data collected were analyzed descriptively and presented in frequency distribution tables along with narrative descriptions to clearly illustrate the distribution of blood glucose levels among these patients. The results indicate that out of 30 patients, 19 individuals (63%) had blood glucose levels within the normal range (70-110 mg/dL), while 11 individuals (37%) showed elevated blood glucose levels (>110 mg/dL). These findings suggest that most TB patients with DM have blood glucose levels within the normal range, although a portion experienced elevated levels. In conclusion, routine blood glucose monitoring is essential for TB patients with DM to prevent further complications and maintain stable health conditions.